Slurry Erosion Behaviour of Pack Boronized 13-4 Martensitic Stainless Steel for Hydro Turbine Blades. (2018) - Nath, Gaurav; Kumar, Satish
Abstract: Pack boronizing of hydro turbine blade steel i.e. 13Cr-4Ni martensitic stainless steel (13-4 MSS) has been conducted as a protective coating against silt erosion. A boride coating of approximately 40 µm was deposited on the samples. Slurry pot method was used to evaluate the erosive wear resistance in which samples were rotated in an abrasive slurry of 100 g/litre silica sand (size 210 – 297 µm) in water at a speed of 4.45 m/s for a period of 40 hrs. Higher wear resistance of pack boronized 13-4 MSS has been attributed to the higher hardness of boride coating (2300 VHN) over that of bare 13-4 MSS (345 VHN).